EVALUASI DAN AKUMULASI LOGAM BERAT PADA ANADARA GRANOSA DAN ANADARA INAEQUIVALVIS DI PERAIRAN KOTA TARAKAN - Ratno Achyani; Gazali Salim (Jurnal Harpodon Borneo, 2014)
The aim of this study was to determine the presence and concentration in waters and sediments, especially accumulation at bivalves Anadara Granosa (Linnaeus, 1758), and Anadara inaequivalvis (Brugiere, 1789) in waters of Tarakan City. From analysis of heavy metals in water was detected (concentration on ppm) are Cd 0,067, Cu 0,013, Fe 0,028 and Ni 0,015.  Heavy metals detected in sediment are Cd 0,099, Pb 0,126, Cu 0,689, Fe 0,463, Mn 0,169, and Ni 0,110. Heavy metals were detected in bodies at small weight Anadara Granosa is Cd 0,043, Cu 0,011, Fe 0,224 and Mn 0,017.  From Average Weight is Cd 0,064, Cu 0,012, Fe 0,224, Mn 0,017 and Ni 0,096 and high weight are Cd 0,072, Cu 0,026, Fe 0,285, Mn 0,102 and Ni 0,254.  Heavy metals were detected in bodies Anadara inaequivalvis at small weight is Cd 0,081, Cu 0,028, Fe 0,253, Mn 0,012 and Ni 0,011. In average weight is Cd 0,089, Cu 0,075, Fe 0,254, Mn 0,030 and Ni 0,014 and the large weight is Cd 0,097, Cu 0,102, Fe 0,254, Mn 0,033 and Ni 0,018. Status on concentrations of heavy metals in water, sediment and Anadara Granosa and Anadara inaequivalvis generally still below the quality standard required.Keywords: Heavy Metals, sediments, waters, Anadara granosa (Linnaeus, 1758), Anadara inaequivalvis (Brugiere, 1789)